Polityka finansowa gminy w procesie stymulowania rozwoju lokalnej przedsiębiorczości - Wartalska, Magdalena (Commune's financial policy in the process of development stimulation of local enterpreneurship, 2006)
The problem in this article is dedicated to the role and importance of actively developing financial policy by local authorities in aim of supporting a local entrepreneurship. It does not matter if it is large city agglomeration or a small village commune, all local authorities have possibilities to use a number of financial instruments, which goal is to encourage local economy development. In this situation instruments related to budget are most often taken under consideration. Conscious policy to create economy in regards to revenue and expenses may in important way have bearings on local entrepreneurship development. Systemic solutions made by territorial self-government units, which are encouraging investment, may surprisingly quickly be used by entrepreneurs. It is relevant to remember that in conditions of market economy investing individuals are intent observers, who see potential profits and chances for development of their businesses and who can take advantage of coming occasions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 314-321